DESIGN ELEMENTS IN FLEXIBLE DIGITAL MODEL (MFD) COURSES FOR STUDENT ENGAGEMENT IN INDUSTRIAL AND SYSTEMS ENGINEERING PROGRAM (Proceedings of the International Conference on Education, 2021)
Crisis caused by COVID-19 forced academics to transform Face-to-face education into digital education. As most of the courses had been never taught this way, professors needed to learn how to interact with students, and teach the academic content within a virtual platform. There was a major concern about how these online synchronous sessions had to be delivered, as well as which elements were critical for knowledge transfer and add value to the Industrial and Systems Engineering (ISE) courses. For having a proper feedback about this format, an instrument was created to evaluate the design course elements, based on theoretical approaches of teaching and learning processes in higher education, particularly on student experiences. The instrument consisted of a survey applied to ISE students from Tecnologico de Monterrey. The analysis considered the nature of the different courses involved in the study, and their categorization as Theoretical, Numerical or Mixed. After applying statistical analysis, some of those elements showed a positive evaluation by students and considering the correlations among them, recommendations for the design of Digital Flexible Model (MFD) courses are made. A positive correlation has been found between active participation of the students, voluntary participation, and the sense of involvement, as well as the ease of interacting that the technological platform provided to the students. Among other results, highlighting the usage of a technological platform is not enough to deliver MFD courses, it is necessary to consider design elements for engaging and motivating students’ participation. It is notorious for the need for a "holistic" transversal approach that complements the design of the successful interaction experience of students in the MFD.
Keywords: Digital Education; MFD (Digital Flexible Model); Education in pandemic; Educational Innovation; Higher Education; Students engagement